Public agreement in the rendering of paid medical services to people - Ye. A. Rabtsun (Бюллетень сибирской медицины)
The position that the agreement on the rendering of paid medical services to people (physical persons) is a public agreement is justified. The public agreement differs in its legal order of performance from the ordinary agreement on the paid rendering of (medical) services. The writing form and handling procedures of this agreement are also different.